Local governments' revenue and expenditure autonomy as a determinant of local public spending on culture. An analysis for Polish rural municipalities - Kopańska, Agnieszka (European Journal of Multidisciplinary Studies, 2022)
The aim of this paper is to define expenditure and revenue decentralization indicators for Polish municipalities and to analyze if and how the limits of spending and revenue autonomy influence local government spending behaviors. The expenditure decentralization is difficult to measure, that is why the analysis of the effects of limits on spending autonomy are less common in the literature than those which relate to the revenue autonomy. In this paper, I propose indicators of revenue but also expenditure decentralization for Polish municipalities. Using statistical analysis and econometric panel analysis for rural municipalities in years 2000-2014 I study if and how these indicators explain local spending policy. I focus on spending for culture using median voter demand framework. Expenditure for culture is a small part of local budgets, but vital from the social point of view. Municipalities in Poland are important creators of local cultural life, which is especially important in less developed or peripheral regions, where citizens do not have access to private cultural institutions. I present that limits in local governments spending and revenue autonomy influences the local spending behaviors. I found that those limits caused not necessarily effective cost minimizing and create the important problem of horizontal equity. At the same time in less autonomous municipalities spending are less related to citizens demand- so there are problems to attend allocative efficiency. My study presents that the problem of the effects of incomplete expenditure decentralization is very important but poorly recognized in the literature.
Keywords: public expenditure on culture, local governments’ autonomy, fiscal federalismAcknowledgement: The study is part of research project No. 2014/13/B/HS4/03204, financed by National Science Centre, Poland